A Facile Method to Produce N-Terminally Truncated α-Synuclein - Thrush, Rebecca J.; Vadukul, Devkee M.; Aprile, Francesco A. (Frontiers in Neuroscience, 2022)
α-Synuclein is a key protein of the nervous system, which regulates the release and recycling of neurotransmitters in the synapses. It is also involved in several neurodegenerative conditions, including Parkinson’s disease and Multiple System Atrophy, where it forms toxic aggregates. The N-terminus of α-synuclein is of particular interest as it has been linked to both the physiological and pathological functions of the protein and undergoes post-translational modification. One such modification, N-terminal truncation, affects the aggregation propensity of the protein in vitro and is also found in aggregates from patients’ brains. To date, our understanding of the role of this modification has been limited by the many challenges of introducing biologically relevant N-terminal truncations with no overhanging starting methionine. Here, we present a method to produce N-terminally truncated variants of α-synuclein that do not carry extra terminal residues. We show that our method can generate highly pure protein to facilitate the study of this modification and its role in physiology and disease. Thanks to this method, we have determined that the first six residues of α-synuclein play an important role in the formation of the amyloids.